MAKNA SIMBOL ATRIBUT FPI DIKALANGAN ANGGOTA ORGANISASI MASYARAKAT FRONT PEMBELA ISLAM DI KOTA PEKANBARU - Orandi Saputra; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Front Pembela Islam started to reveal openly at 1990. This matter was marked with the existence of recitation community by wearing clothes that cover aurat as syari’at in Islam. The organization of Front Pembela Islam who used the symbol of sentence calligraphy “laa ilaaha illallah muhammadurrasulullah” in the star form and above there was calligraphy “bismillahirrahmanirrahim” in hilal form, surrounded by triangle of beads that peak sentence calligraphy “alhamdulillahirabbil’alamin” in mosque dome which all were green colored with white base. In the triangle of beads exactly under the star, there was a black colored script “al-jabhah ad-difaa’iyah al-islamiyyah” and written on Front Pembela Islam was in red color. The purpose of this research was to known what the FPI member’s motive to join, how FPI attribute symbols mean to FPI members and how FPI members' loyalty to FPI organization in Pekanbaru City.This research used Cualitative Method with Alfred Schutz phenomenology approach and George H Mead interaction symbolic theory. The total informant was consisted of five person as a key informant by using snowball sampling technique. Data collection technique was by interview, observation, and documentation. This research used Miles and Huberman data analysis model through data reduction, display data or presentation data and last taking conclusion or verificationThe result of this research pointed out that the members’ motive to join Front Pembela Islam organization divided into two; because motive and in order to motive. The Meaning of attribute symbol for FPI members at Pekanbaru is also divided into two divvy. First is as a fighting spirit symbol. Second is as a holiness symbol. The Members’ loyalty can be shown their ways in following organization activities. First is following majlis taklim which purposed to sharing about Islam religion knowledge. Second is following training which is held by Front Pembela Islam regional city or province. Third is by dakwah or preaching from mosque to other mosque and also participate to maintain amar ma’ruf nahi munkar. And the last is following “isbah” which do explicit action in every places forbidden by Islam religion, of course in a way giving warning before doing next steps.keyword : phenomenology, Interaction Symbolic, Front Pembela Isla